PENGARUH LINGKUNGAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI - Muh. Pradana Ismunandar; Murdjani Kamaluddin; Endro Sukotjo (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2018)
This study aims to test and analyze: (1). The influence of the work environment on the performance of the Kolaka Regency Regional Secretariat employees, (2). The influence of work discipline on the performance of the employees of the Regional Secretariat of Kolaka Regency, this study used as many as 63 employee respondents. While the data analysis used descriptive analysis and inferential analysis Multiple Linear Regression using SPSS software.The results of this study are (1). The work environment has a significant effect on the performance of the Kolaka Regency Regional Secretariat employees, (2). Work discipline has a significant effect on the performance of the Kolaka Regency Regional Secretariat employees.Keywords: Work environment, workdicipline, employees performance